The Application of Local Culture-Based Character Education at SMAN 4 Enrekang - Mustakim Mustakim; Hasan Hasan (Universitas Muhammadiyah Enrekang, 2020)
Character is an important factor of future human progress. Character education has become a main issue in education, beyond being part of the learning process of shaping the morals of the children of the country, character education is now expected to be the principal foundation of Indonesia Gold 2025 's success. Various studies and facts show that the developed nation is a nation that has strong character. These character values are values that are extracted from cultural treasures that are in harmony with the characteristics of the local culture and not to